2020
DOI: 10.3390/ani10020339
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of the Inclusion of Silage Artichoke By-Products in Diets of Dairy Goats on Milk Quality

Abstract: Artichoke by-products represent a high amount of waste whose removal entails several costs. Moreover, feed is the main cost in a farm. So, including these by-products in ruminant diets would lower feed costs. Two experiments were conducted to evaluate the effect of two levels of inclusion, 12.5% and 25.0%, of two silages of artichoke by-products (artichoke bracts, AB and artichoke plant, AP) in the diet of goats on the milk yield, composition and quality and on the metabolic profile of the animals. AB presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 38 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…BB animals showed a lower feed consumption than C and AP animals, because the diet that included BB contained a higher concentration of fermentation products, such as acetic acid, ethanol and ammonia N (Table 1), which had a depressive effect on feed consumption, as observed by Huhtanen et al [38] through a meta-analysis of 240 studies. As in Monllor et al [20], the higher moisture content of the BB diet and, therefore, the higher ration volume, decreased consumption. Other causes that affected feed consumption were the higher content of polyphenols in BB, which limits intake, as observed by Oliveira et al [39] in growing calves and in grazing Sardinian goats, as shown by Decandia et al [40].…”
Section: Body Weight and Milk Performancesupporting
confidence: 51%
See 4 more Smart Citations
“…BB animals showed a lower feed consumption than C and AP animals, because the diet that included BB contained a higher concentration of fermentation products, such as acetic acid, ethanol and ammonia N (Table 1), which had a depressive effect on feed consumption, as observed by Huhtanen et al [38] through a meta-analysis of 240 studies. As in Monllor et al [20], the higher moisture content of the BB diet and, therefore, the higher ration volume, decreased consumption. Other causes that affected feed consumption were the higher content of polyphenols in BB, which limits intake, as observed by Oliveira et al [39] in growing calves and in grazing Sardinian goats, as shown by Decandia et al [40].…”
Section: Body Weight and Milk Performancesupporting
confidence: 51%
“…For the analysis of dietary and milk minerals, the same procedures were followed as in Monllor et al [20], with a previous digestion of the samples performed according to González Arrojo et al [4]. Na, Mg, K, Ca, P, S (g/kg DM) and Se, Zn, Cu, Fe and Mn (mg/kg DM) were determined by prior microwave digestion (Ethos Easy, Milestone, Italy) and identified with an ICP-MS octupole chromatograph (Agilent 7500 Reaction System, USA), using an internal standard.…”
Section: Variables Analysedmentioning
confidence: 99%
See 3 more Smart Citations